An unusual late onset of pulmonary alveolar microlithiasis: A case report and literature review. (2017) - Stamatopoulos, Alexandros; Patrini, Davide; Mitsos, Sofoklis; Khiroya, Reena; Borg, Elaine; Hayward, Martin; Lawrence, David; Panagiotopoulos, Nikolaos
Abstract: Pulmonary alveolar microlithiasis (PAM) is an uncommon genetic disorder associated with alveolar cell injury. This injury is caused in most cases by inactivating mutations in SLC34A2 gene, which is responsible for the production of a sodium-dependent phosphate co-transporter. The dysfunction or deficiency of this transporter leads to the aggregation of local phosphate intra-alveolarly and formation of microliths. Most of the patients are asymptomatic at the time of the diagnosis but as the disease progress it leads to fatal respiratory or cardiac failure. We describe a case of a 63-year-old man referred to our department for a surgical lung biopsy. He has been symptomatic for one year with progressive shortness of breath and deteriorating exercise tolerance. The imaging was suggestive of extensive interstitial bilateral lung disease. Histological findings after the lung biopsy by video-assisted thoracic surgery (VATS) established the diagnosis of pulmonary alveolar microlithiasis. His sister suffered from the same disease and passed away at the age of 54. It is remarkably rare for PAM to have such a late onset with a previous normal X-ray and only a few cases have been reported worldwide.